Removal of Particulate Matter in a Tubular Wet Electrostatic Precipitator Using a Water Collection Electrode - Jong-Ho Kim; Hee-Jung Yoo; You-Seong Hwang; Hyeok-Gyu Kim (The Scientific World Journal)
As one of the effective control devices of air pollutants, the wet electrostatic precipitator (ESP) is an effective technique to eliminate acid mist and fine particles that are re-entrained in a collection electrode. However, its collection efficiency can deteriorate, as its operation is subject to water-induced corrosion of the collection electrode. To overcome this drawback, we modified the wet ESP system with the installation of a PVC dust precipitator wherein water is supplied as a replacement of the collection electrode. With this modification, we were able to construct a compact wet ESP with a small specific collection area (SCA, 0.83 m2/(m3/min)) that can acquire a high collection efficiency of fine particles (99.7%).